Development Strategy of Islamic Civil Society Organization (CSO) In Indonesia: A Case of Al Jamiyatul Al Wasliyah - Harahap, Nursapia; ., Warjio; Ginting, Junita Setiana; Abdullah, Zaharul; Raihan, Haykal M. (Journal of Ecohumanism, 2024)
One of the largest Islamic organizations in Indonesia, Jamiyatul Alwasliyah, has a large identity and role in the development of Indonesia, even before Indonesia's independence. In fact there are not many researchers who pay attention to the political role of this organizational development. In reality, Jamiyatul Alwasliyah was formed with the spirit of advancing the nation and they succeeded with their development identity. This article, with a historical approach, will explain the background and political role of their development in Indonesia. This article examines some of the main political themes addressed in the NGO literature, as well as related themes in other political studies. This article analyses its development based on Islamic spirit and development strategy. It begins by examining competing theories regarding the political impact of the NGO sector. The article argues, make significant contributions of Jamiyatul Al Wasliyah as Civil Society Organization (CSO) to political life and to political change in developing countries, revealing a fertile, and hitherto neglected, research agenda.